The relationship between health belief and sleep quality of Chinese college students: The mediating role of physical activity and moderating effect of mobile phone addiction - Gao, Xinchao; Li, Chuang; Han, Beining; Xu, Peng; Qu, Chenxu (Frontiers in Public Health, 2023)
Background: Poor sleep quality has become a common health problem encountered by college students. Methods: Health Belief Scale (HBS), Physical Activity Rating Scale (PARS-3), Mobile Phone Addiction Tendency Scale (MPATS) and Pittsburgh Sleep Quality Index (PSQI) were adopted to analyze the data collected from survey questionnaires, which were filled out by 1,019 college students (including 429 males and 590 females) from 5 comprehensive colleges and universities from March 2022 to April 2022. The data collected from survey questionnaires were analyzed using SPSS and its macro-program PROCESS. Results: (1) Health belief, physical activity, mobile phone addiction and sleep quality are significantly associated with each other (P＜0.01); (2) Physical activity plays a mediating role between health belief and sleep quality, and the mediating effects account for 14.77%; (3) Mobile phone addiction can significantly moderate the effect size of health belief (β= 0.062, P<0.05) and physical activity (β=0.073, P＜0.05) on sleep quality, and significantly moderate the effect size of health belief on physical activity (β= - 0.112, P<0.001). Conclusions: The health belief of college students can significantly improve their sleep quality; college students' health belief can not only improve their sleep quality directly, but also improve their sleep quality through physical activity; mobile phone addiction can significantly moderate the effect size of health belief on sleep quality, the effect size of health belief on physical activity, and the effect size of physical activity on sleep quality.